Modeling the distribution and probability of aflatoxin occurrence using environmental data - Masuoka, Penny; Chamberlin, Judith; Elias, Maribel (International Food Policy Research Institute, 2010)
Aflatoxins, which are produced by Aspergillus molds, depend on environmental conditions in order to thrive. These toxins occur under drought conditions, when plants are more vulnerable to colonization by Aspergillus (Sanders et al. 1993), and post-harvest storage conditions that involve high humidity.